Pembelajaran Berbasis Dongeng Dalam Membentuk Akhlak Islami Siswa di SD - Zulfitria Zulfitria; Zainan Arif; Maesaroh Lubis; Tyasti Aryandini (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2022)
Morals or character is the main basis in the formation of a complete human personality. Humans who have commendable character can maintain the glory and sanctity of their souls. A soul that is always developing can overcome the pressure of lust to do something not commendable. The purpose of this study is to apply a fairy tale-based learning model in the formation of Islamic character to students. Students who have good characters such as helping to help, respecting parents, loving the young, happy with truth and justice, tolerance, keeping promises and honesty are highly coveted by parents and teachers. zIn zthe zformation zof zIslamic zcharacters, zresearch zis zcarried zout zusing za zfairy ztale-based zlearning zmodel. zThe zteacher ztells zthe zstudents zthe zcompanions zof zthe zProphet zSAW zwho zhave znoble zcharacter. zThis zresearch zwas zconducted zat zSDIT zAulady zSerpong zBanten zin zgrade z3 zSD. zThe zstudy zused za zqualitative zapproach zto zobtain zan zin-depth zdescription zof zthe zproblems zthat zoccurred zby zusing zdata zcollection zin zthe zform zof zobservations, zinterviews zand zdocumentation. zFrom zthe zresults zof zthe zresearch zconducted, zit zcan zbe zconcluded zthat zfairy ztale-based zlearning zis zvery zeffective zin zshaping zIslamic zmorals zin zstudents, zthis zcan zbe zseen zin zchanges zin zstudent zbehavior zto zbe zmore zenthusiastic zabout zlearning, zmaintaining zcleanliness, zhappy zto zgive zalms zand zworship zbecause zthey zwant zto zfollow zthe zcharacter zof zthe zcompanions zof zthe zProphet zSAW.